2008
DOI: 10.1007/s12053-008-9032-8
|View full text |Cite
|
Sign up to set email alerts
|

Industrial energy efficiency and climate change mitigation

Abstract: Industry contributes directly and indirectly (through consumed electricity) about 37% of the global greenhouse gas emissions, of which over 80% is from energy use. Total energy-related emissions, which were 9.9 GtCO 2 in 2004, have grown by 65% since 1971. Even so, industry has almost continuously improved its energy efficiency over the past decades. In the near future, energy efficiency is potentially the most important and cost-effective means for mitigating greenhouse gas emissions from industry. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
151
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 361 publications
(158 citation statements)
references
References 31 publications
1
151
0
6
Order By: Relevance
“…Moreover, reduced energy costs are crucial for industrial companies in maintaining a competitive advantage [5,6]. Increased energy efficiency can arrive from technological improvements [7], improved supply chain management [8], and the implementation of environmental management systems (EMS) [9], environmental regulation [10], and economic motives [6]. The first electronic database search, after the removal of duplicates, resulted in 835 articles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reduced energy costs are crucial for industrial companies in maintaining a competitive advantage [5,6]. Increased energy efficiency can arrive from technological improvements [7], improved supply chain management [8], and the implementation of environmental management systems (EMS) [9], environmental regulation [10], and economic motives [6]. The first electronic database search, after the removal of duplicates, resulted in 835 articles.…”
Section: Introductionmentioning
confidence: 99%
“…Companies support the concept of environmental sustainability which coordinates social factors with profit occasions. The implementation of resource-efficient technologies develop the competitiveness of a business and the green production phases have been combined to higher returns on investment funds and expanded kinds of sales (Worrell et al, 2009). …”
Section: Why Firms Go Greenmentioning
confidence: 99%
“…Barriers impeding improvements in energy efficiency issues need to be lowered to bridge this gap. A number of studies have already revealed the considerable potentials of energy-efficiency measures (Blok 2004;Grenade et al 2009;Worrell et al 2009;Fraunhofer ISI et al 2014;Ecofys and Fraunhofer ISI 2010;Eichhammer 2013). Accordingly, improving energy efficiency has received increasing attention in energy policy in many countries (IEA 2012).…”
Section: Introductionmentioning
confidence: 99%